BS ISO 4825-1. Fine ceramics (advanced ceramics, advanced technical ceramics). Test method for thermal property measurements of metalized ceramic substrates. Part 1. Evaluation of thermal resistance for use in power modules (17th March 2022) - British Standards Institution,
No abstract available